2019
DOI: 10.1111/apt.15314
|View full text |Cite
|
Sign up to set email alerts
|

Review article: emerging role of the gut microbiome in the progression of nonalcoholic fatty liver disease and potential therapeutic implications

Abstract: Summary Background Nonalcoholic fatty liver disease (NAFLD) is a prevalent disorder associated with obesity and diabetes. Few treatment options are effective for patients with NAFLD, but connections between the gut microbiome and NAFLD and NAFLD‐associated conditions suggest that modulation of the gut microbiota could be a novel therapeutic option. Aim To examine the effect of the gut microbiota on pathophysiologic causes of NAFLD and assess the potential of microbiota‐targeting therapies for NAFLD. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 173 publications
(269 reference statements)
1
54
0
7
Order By: Relevance
“…Soderborg et al also found that these colonized mice had increased periportal inflammation, which correlated with an increased modified pediatric NAFLD histological score [ 121 ] and increased collagen disposition around the portal triad [ 122 ] compared with mice colonized with stool from 2-week-old infants from normal-weight mothers. In the liver, LPS infiltration leads to pro-inflammatory cytokine production and liver Kupffer cell (KC) activation, which can lead to the activation of hepatic stellate cells and fibrosis [ 123 ]. These results support the concept that early maternal microbial dysbiosis contributes to the detrimental effects on offspring immune function that can drive hepatic inflammation.…”
Section: Gut Microbial Dysbiosis In Pediatric Nafldmentioning
confidence: 99%
“…Soderborg et al also found that these colonized mice had increased periportal inflammation, which correlated with an increased modified pediatric NAFLD histological score [ 121 ] and increased collagen disposition around the portal triad [ 122 ] compared with mice colonized with stool from 2-week-old infants from normal-weight mothers. In the liver, LPS infiltration leads to pro-inflammatory cytokine production and liver Kupffer cell (KC) activation, which can lead to the activation of hepatic stellate cells and fibrosis [ 123 ]. These results support the concept that early maternal microbial dysbiosis contributes to the detrimental effects on offspring immune function that can drive hepatic inflammation.…”
Section: Gut Microbial Dysbiosis In Pediatric Nafldmentioning
confidence: 99%
“…Importantly, these pathways can influence disease phenotype in a diverse fashion, thus determining disease heterogeneity . Several studies have highlighted the role of the gut microbiota in NAFLD . Preclinical studies have shown that germ‐free mice are protected against obesity and hepatic steatosis .…”
Section: Introductionmentioning
confidence: 99%
“…Comparative metagenomics aims to study the diversity of microbes through large-scale sequencing of microbial communities; in the case of this study, the communities studied were part of the gut microbiota (Huson et al 2009, Turnbaugh et al 2008. Similar studies conducted in children and adults have shown correlations between gut microbe composition and diseases, such as type-2 diabetes, obesity, IBS, and inflammation (Lambert et al 2015, Durack and Lynch 2019, Jayakumar and Loomba 2019, Cooper et al 2017.…”
Section: Current Uses Of Fermentation In Medicinementioning
confidence: 99%
“…The study of the human gut microbiome has increasingly become a topic of interest for researchers worldwide, including the effects of fermented products on the composition of the gut microbiome. Gut microbiota can be correlated to IBDs such as Crohn's Disease (CD), and other diseases such as Non-Alcoholic Fatty Liver Disease, and diabetes (Lambert et al 2015, Durack and Lynch 2019, Jayakumar and Loomba 2019. Dysbiosis is increasingly being implicated in varying forms of IBD, where the loss of enteric bacterial diversity and an expansion in the relative abundance of family Enterobacteriaceae has been associated with the onset of CD (Durack and Lynch 2019).…”
Section: Current Uses Of Fermentation In Medicinementioning
confidence: 99%